RESPON PERTUMBUHAN DAN PRODUKSI JAGUNG (Zea mays L.) HIBRIDA PADA TINGKAT POPULASI YANG BERBEDA (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
The study, entitled : Response Growth and Production of Maize ( Zea mays L ) Hybrids at Different Population Levels " . Aims to obtain an optimal population ( maximum production ) on corn hybrids , and review of the type of corn on the density of population of different levels . The research was conducted in October 2014 until June 2015 , housed in the land Agro Technology Center ( ATP ) Hyacinths Village , District Inderalaya , Ogan Ilir ( OI ) South Sumatra Province . The design used the design is divided ( Split Plot Design ) with two main plots , nine sub- plots and repeated 3 times . The results showed that the growth of hybrid corn varieties generally yield maximum production is achieved in a population of 80,000 / ha yield 7.1 tons / ha dry seed .Â Key words Â : Response Growth, Production of Maize